Antimutagenicity and anticlastogenicity of glutinous purple rice hull using in vitro and in vivo testing systems - Sankam P. (2014)
Glutinous purple rice (Oryza sativa L.var. indica) contains high amounts of nutrients and phytochemicals. Rice hull is a low-value waste product, yet contains many bioactive ingredients. The genotoxicity and antigenotoxicity of the dicholoromethane extract of glutinous purple rice hull were investigated. The amounts of phenolic compounds, flavonoids and γ-oryzanol of hull extract were 174.0±55.0, 220.0± 7.5, and 23.6±0.1 mg/g extract, respectively. Lower amounts of tocopherols and tocotrienols were detected. The mutagenicity and antimutagenicity of the extract were determined using a Salmonella mutation assay. Rice hull extract was not mutagenic in either strain TA98 or TA100 in the presence and absence metabolic activation. The extract showed antimutagenicity against AFB1 and MeIQ, but did not against AF-2 and NaN3. It enhanced the mutagenic activity of benzo(a)pyrene in TA100 with metabolic activation. The toxicity and genotoxicity of dichloromethane extract of glutinous purple rice hull were further studied in an animal model. The extract was non-toxic to rats at a single dose of 2000 mg/kg bw of extract following the OECD Guideline 425 protocol. The clastogenicity and anticlastogenicity of the extract were studied using a rat liver micronucleus assay. The oral administration of 500 mg/kg bw of glutinous purple rice hull extract for 28 days did not affect the number of micronucleated hepatocytes or mitotic index in rats, but it significantly decreased the number of micronucleated hepatocytes in diethylnitrosamine-initiated rats. Furthermore, the dichloromethane rice hull extract significantly enhanced glutathione-S-transferase activity in the livers of diethylnitrosamine-initiated rats. In conclusion, dichloromethane extract of glutinous purple rice hull presented antimutagenic and anticlastogenic potential. The inhibitory mechanism of this rice hull extract might be partly due to either induction of detoxifying enzymes or inhibition of metabolizing enzymes. © 2013 The Korean Society of Toxicogenomics and Toxicoproteomics and Springer Science+Business Media Dordrecht.